Anthroponymy evolution of Javanese diaspora names in Malaysia (social onomastics study) - Widodo, Sahid Teguh; Suyatno, Suyatno; Mohamad, Bahtiar; Ismail, Shafinar (Frontiers in Sociology, 2023)
The personal name of the Malaysian Javanese Diaspora (MJD) grows and develops along with the history of dynamic life, thought, social, and cultural developments. This research specifically aims to reveal and explain the process of anthroponymy evolution of the Javanese-Malaysia diaspora personal name system from historical, social, cultural, and linguistic characteristics aspects and the meaning of personal names that developed due to the cultural shifts and changes. This research utilizes data sources from lists of names of Javanese diaspora communities and efforts to extract names from MJD people who are in the locations of the states of Johor, Selangor, and Melaka in Peninsular Malaysia. Data were collected using content analysis techniques and in-depth interviews through discussions and Focus Group Discussions (FGD) as well as informal meetings directly at the research location. The results of the study show that the forms of names that appear in MJD society are strongly influenced by historical, social, and cultural phenomena that developed in the era before and after Malaysia's independence. This phenomenon affects the characteristics of personal names so that it can be seen that there are phases of MJD people's names, namely the initial arrival phase, the transition phase, the modern phase, and the latest phase. The results of this study can be used to find out the development of thought, spirit of life, and cultural traditions of a large MJD collective in Peninsular Malaysia.